Participation in and outcomes from a 12-month tailored exercise programme for people with multiple sclerosis (MSTEP©): a randomized trial. (July 2020) - Mayo, Nancy E; Mate, Kedar KV; Reid, Ryan; Duquette, Pierre; Lapierre, Yves; Barclay, Ruth; Bayley, Mark; Bartlett, Susan; Andersen, Ross
Objective: To estimate, among people with multiple sclerosis, the extent to which a personally tailored exercise programme (MSTEP©) resulted in greater improvements in exercise capacity and related outcomes over 12 months in comparison with general exercise guidelines. Design: Two-group randomized trial. Subjects: Ambulatory and sedentary. Interventions: MSTEP©, a personally adapted exercise regimen done on most days including two days of high intensity exercise; guidelines recommending 30 minutes of moderate intensity aerobic and strength training two times per week. Main measures: Primary outcome was peak oxygen consumption (VO2peak ) at 12 months; secondary outcomes were composite measures of physical function, fatigue, and health-related quality of life. Results: In total, 137 people were randomized, 66 were lost over 12 months leaving 71 with outcome data, 34 in MSTEP© group, and 37 in the Guideline group. Exercise enjoyment and confidence and exercise-induced fatigue predicted retention. There were no differences between groups on the proportion making a 10% increase in VO2peak (27.1% MSTEP© vs 29.6% Guidelines; OR: 0.83; 95% CI: 0.23–3.08) by the 12 month assessment. The effect on fatigue was larger in the MSTEP© group than the Guideline groups (OR: 1.59; 95% CI: 0.93–2.74), the effect on physical function was more modest (OR: 1.35; 95% CI: 0.80–2.25), and null for health-related quality of life outcomes. Conclusions: The disappointing exercise retention suggests that people with multiple sclerosis may not consider exercise important to their brain health. Either type of exercise resulted in stable exercise capacity over 1 year in those sticking with the programme.